Analisis pemahaman konsep matematika materi pecahan ditinjau dari gaya belajar kelas IV sekolah dasar - Berliana Dewi Riang Andaru; Joko Daryanto (Universitas Sebelas Maret, 2026)
This study aims to describe the understanding of mathematical concepts of fractions in terms of learning styles. This study uses a qualitative descriptive method. The study was conducted on six fourth-grade students at SDN O3 Jatipuro as subjects. The data used are qualitative data with descriptive presentation in the form of oral data collection techniques using questionnaires, interviews, observations, documentation, and mathematics test results documents. The validity test technique uses method triangulation. Data analysis uses data analysis techniques proposed by Miles and Huberman, namely data collection, data reduction, data presentation, and drawing conclusions or verification. The results of this study prove that there are variations in the achievement of conceptual understanding indicators in each learning style, namely visual, auditory, and kinesthetic.